Characteristics of Mothers Before and During Pregnancy Causing Postpartum Hemorrhage in Surabaya, Indonesia - Dhiana Setyorini; Intim Cahyono; Nur Hasanah (Humanistic Network for Science and Technology (HNST), 2020)
Postpartum hemorrhage (PPH) is one of the direct causes of maternal mortality with the highest percentage. Postpartum hemorrhage is the bleeding that occurs due to the blood loss of 500 ml or more from the reproductive organs after labor. The objective of this present research was to understand the characteristics of mothers before and during pregnancy that induce postpartum hemorrhage in Surabaya. The research method employed was a control case design consisting of 180 postpartum mothers, being analyzed using a multinomial logistic regression. The research was conducted in Soewandi Hospital and Haji Hospital Surabaya. The research results revealed that characteristics of mothers before pregnancy causing the incidence of postpartum hemorrhage were as follows: a) Age < 20 and > 35 (66.7%), b) multi-parity (61.14%), pregnancy spacing ≤ 24 months (70.4%), d) possessing postpartum hemorrhage history (93.3%) and e) suffering from anemia (80.8%). Characteristics of mothers during pregnancy were among others : Double pregnancy (71.4%), preeclampsia (79.5%) and obesity (70.6%). It is expected that the cadres of health staffs recognize the characteristics of these mothers and are able to detect earlier any postpartum hemorrhage that occurs to pregnant women so that earlier prevention actions may be taken. Keywords: causing factor; before and during pregnant; postpartum hemorrhage